Evaluation of Rationality in Prescribing Metformin (Biguanide Group) at Dr. Mohammad Hoesin General Hospital Palembang - Nita Parisa; Dwi Tantri Marylin; Theodorus (HM Publisher, 2022)
Backgrounds. It is very important to evaluate and assess the rationality of the use of antidiabetic drugs, especially the biguanide (metformin) group to maintain the quality and quality of diabetes mellitus drug administration so that the target of diabetes mellitus control can be optimized. This study aims to evaluate the rationality of prescribing metformin oral antidiabetic at Dr. Mohammad Hoesin General Hospital Palembang. Methods. The research design is a descriptive study using secondary data from medical records in the medical records section of Dr. Moh Hoesin Hospital Palembang. The object of research is all medical records of patients with type 2 diabetes mellitus who used metformin at RSMH Palembang in the period July 1st, 2019-July 31st, 2020, with complete medical record data and without serious comorbidities. The rationality for using metformin that was assessed in this study was the frequency of use, drug dose, route of administration, duration of administration, and drug interactions. The frequency of drug use is assessed by how many times the drug is taken in one day. Results. The most age group of patients who received a prescription for metformin were 51-60 years old and 61-70 years old with a total of 17 patients (35.4%). The majority of patients were female as much as 60.4%. Drug interactions with metformin are still quite common, although the majority are synergistic and potentiating interactions. There are still 2 cases or 4.2 percent who experience antagonistic interactions. Conclusion. The rationality for using metformin in patients with type 2 diabetes mellitus is based on the criteria for the right dose (100%), the right frequency of drug administration (100%), the right time for giving the drug (100%), the right way of giving the drug (100%), and the right drug interaction. (95.8%).